Development of Man-Machine Interface using Matlab: an adaptive network-based fuzzy inference system modeling for laser machining - Sivarao; Rizal, M.S.; Tajul, A.; Taufik (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.